Foamed polystyrene-containing thermal insulation material and use thereof
Patent Information
- Application Number
- CN202611085085.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-27
AI Technical Summary
本发明通过构建碳酸钙核-磷酸钙内壳-海泡石外壳的三层核-壳结构复合阻燃剂,并结合特定的改性发泡剂与双阶侧喂料工艺,实现了保温材料在低导热系数与高阻燃等级之间的平衡。具体的,
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal insulation materials technology, and relates to a thermal insulation material containing expanded polystyrene and its application. Background Technology
[0002] Expanded polystyrene (EPS) insulation materials are widely used in the field of building exterior wall energy conservation, and have become the mainstream insulation material due to their advantages such as light weight, low thermal conductivity, and convenient construction. However, ordinary EPS insulation materials have a low limiting oxygen index, are flammable, and produce severe dripping and large amounts of smoke when burning, posing significant safety hazards in building energy conservation projects and limiting their further application in high-rise and public buildings.
[0003] To improve the flame retardant properties of EPS insulation materials, traditional flame retardants such as aluminum hydroxide, ammonium polyphosphate, and expandable graphite are often added in the industry. However, these flame retardants require large amounts and have poor compatibility with polystyrene, which can easily lead to an increase in thermal conductivity and affect the insulation effect. At the same time, conventional flame retardants are mostly simple physical blends, which make it difficult to form a stable carbon layer and barrier structure, resulting in low flame retardant efficiency and an inability to achieve a synergistic balance between flame retardant and insulation performance.
[0004] Inorganic minerals such as calcium carbonate and sepiolite are widely available and inexpensive, and are often used as fillers in thermal insulation materials. However, these minerals themselves do not possess flame-retardant activity; they can only serve as fillers and reinforcements, and cannot be used as flame retardants. Current technology has not yet developed a method to construct a three-layer core by phosphorylation-coating calcium carbonate with sepiolite in a confined composite structure. There are reports on shell structures and their high-efficiency flame-retardant properties. Therefore, developing an EPS insulation material that modifies non-flame-retardant minerals into high-efficiency flame retardants and combines low thermal conductivity with high flame retardancy has significant engineering value and market prospects. Summary of the Invention
[0005] This invention proposes a composite flame-retardant system based on a three-layer core-shell structure of calcium carbonate / calcium phosphate / sepiolite, and combines surface modification of foaming agent with a two-stage side-feeding process to prepare an environmentally friendly composite material with both high flame retardancy and excellent thermal insulation performance.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] On the one hand, the present invention provides a thermal insulation material containing expanded polystyrene, which is made from the following raw materials in parts by weight: 45-65 parts expanded polystyrene, 12-25 parts composite flame retardant, 5-12 parts reinforcing filler, 4-8 parts composite foaming agent, 2-5 parts lubricant, and 1-3 parts antioxidant. The composite flame retardant has a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell.
[0008] Preferably, the preparation method of the composite flame retardant includes the following steps: (1) Dry calcium carbonate at 200-300℃ for 2-4 hours to remove surface adsorbed water and obtain activated calcium carbonate; (2) Disperse the activated calcium carbonate obtained in step (1) in a phosphoric acid solution with a mass concentration of 5-20% at a solid-liquid ratio of 1:5-10, add hexadecyltrimethylammonium bromide at a mass of 1-5% of calcium carbonate, stir and react at 60-90℃ for 2-6 hours, so that the calcium carbonate surface undergoes acid-base neutralization precipitation reaction with phosphoric acid, and calcium phosphate coating layer is generated in situ on the surface of calcium carbonate particles, forming a core-shell intermediate with calcium carbonate as the core and calcium phosphate as the shell. Filter, wash and dry to obtain phosphoric acid calcium carbonate; (3) Disperse the calcium carbonate phosphate obtained in step (2) in anhydrous ethanol at a solid-liquid ratio of 1:8-12. Add 5-15% sepiolite powder and 1-3% γ-aminopropyltriethoxysilane by mass of calcium carbonate phosphate. Stir and react at 50-70℃ for 3-6 hours to anchor the sepiolite powder on the calcium phosphate layer on the surface of calcium carbonate phosphate, forming a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell. Filter, wash, and dry to obtain the final product.
[0009] Preferably, the reinforcing filler is selected from one or more of glass fiber and wollastonite.
[0010] More preferably, the wollastonite is SW-10 type wollastonite.
[0011] Preferably, the composite foaming agent is composed of azodicarbonamide and sodium bicarbonate in a mass ratio of 1:0.3-0.8.
[0012] More preferably, the sodium bicarbonate is modified sodium bicarbonate with calcium stearate coated on its surface, and the amount of calcium stearate coating is 3-8% of the mass of sodium bicarbonate; the azodicarbonamide is modified azodicarbonamide activated by zinc oxide, and the content of zinc oxide is 2-5% of the mass of azodicarbonamide.
[0013] Preferably, the lubricant is selected from one or more of zinc stearate and calcium stearate.
[0014] Preferably, the antioxidant is selected from one or more of antioxidant 1010 and antioxidant 168.
[0015] On the other hand, a method for preparing the thermal insulation material according to the present invention is provided, comprising the following steps: Step 1: Premix the composite flame retardant and reinforcing filler in a high-speed mixer at 50-80℃ for 10-20 minutes to obtain premix A; Step 2: Place expanded polystyrene, premix A, lubricant and antioxidant into the main feed port of a twin-screw extruder, and melt-blend at 170-190℃ to establish melt strength and obtain blend B; Step 3: Add the modified azodicarbonamide activated with zinc oxide through the first feed port of the twin-screw extruder, and add the modified sodium bicarbonate coated with calcium stearate through the second feed port of the twin-screw extruder. Control the die head temperature at 140-180℃, and then proceed with melt mixing, extrusion, foaming and shaping, cooling, traction and cutting to obtain the final product.
[0016] The invention also provides the application of the thermal insulation material described herein in the preparation of thermal insulation components.
[0017] The invention also provides the application of the thermal insulation material described herein in improving the flame retardant properties of thermal insulation components.
[0018] It should be noted that in expanded polystyrene materials, low thermal conductivity and high flame retardancy are often contradictory: the addition of flame retardants can disrupt the cell structure and increase the solid-phase heat transfer path, leading to an increase in thermal conductivity. However, this contradiction is not irreconcilable. This invention constructs a three-layer core-shell composite flame retardant with a calcium carbonate core, a calcium phosphate inner shell, and a sepiolite outer shell. The fibrous structure of the sepiolite shell acts as a cell nucleating agent during the foaming process, promoting micropore formation and effectively offsetting the negative impact of flame retardant addition on thermal conductivity, thus achieving a balance between low thermal conductivity and high flame retardancy.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention achieves a balance between low thermal conductivity and high flame retardancy in insulation materials by constructing a three-layer core-shell composite flame retardant consisting of a calcium carbonate core, a calcium phosphate inner shell, and a sepiolite outer shell, combined with a specific modified foaming agent and a two-stage side-feeding process. Specifically, (1) This invention utilizes the microstructure design of composite flame retardants to break the traditional contradiction between flame retardancy and heat preservation. In this system, the sepiolite shell, as a natural one-dimensional nanofiber material, not only plays a physical barrier role in the polymer melt, but more importantly, it serves as a heterogeneous nucleation site. During the foaming process, sepiolite significantly reduces the free energy barrier for bubble nucleation, promoting the formation of a large number of tiny and uniform closed-pore structures. This dense microporous structure greatly extends the heat conduction path, offsetting the increase in thermal conductivity caused by the addition of a large amount of inorganic flame retardant. At the same time, the calcium phosphate inner shell and the calcium carbonate core form a ceramicized carbon layer at high temperature, which, together with the skeletal support of sepiolite, can effectively isolate oxygen and heat transfer during combustion, thereby achieving a high flame retardancy rating with extremely low addition amounts, avoiding the deterioration of heat preservation performance caused by the large-scale filling of traditional flame retardants.
[0020] (2) The preparation method of the thermal insulation material of the present invention is not a simple physical blending, but a process adaptation scheme designed for the characteristics of the modified foaming agent. By injecting azodicarbonamide activated by zinc oxide and sodium bicarbonate coated with calcium stearate separately using a two-stage side feeding method, the decomposition sequence and gas release rate of the two foaming agents in the melt are precisely controlled. This process ensures that the foaming agent only begins to generate gas violently near the highest point of melt strength establishment, preventing premature gas escape or cell merging. Ultimately, a homogeneous microporous structure with high closed-cell rate and narrow pore size distribution is constructed inside the material. As a result, a balance between low thermal conductivity and high flame retardancy can still be achieved even when the amount of composite flame retardant added is 12-25 parts. Detailed Implementation
[0021] The present invention will be described in detail below with reference to specific embodiments and examples, thereby making the advantages and various effects of the present invention clearer. Those skilled in the art should understand that these specific embodiments and examples are for illustrative purposes only and are not intended to limit the present invention.
[0022] The technical solution of the present invention will be described below with reference to embodiments. However, the present invention is not limited to the following embodiments. Unless otherwise specified, the experimental methods and detection methods described in each embodiment are conventional methods; unless otherwise specified, the reagents and materials are all commercially available.
[0023] In this embodiment of the invention, the preparation method of modified sodium bicarbonate coated with calcium stearate is as follows: sodium bicarbonate is dried at 100-110℃ for 1-3 hours to obtain pre-dried sodium bicarbonate; the pre-dried sodium bicarbonate is put into a high-speed mixer and preheated to 50-70℃; calcium stearate equivalent to 3-8% of the mass of sodium bicarbonate is weighed and added to the high-speed mixer in three portions, the mixer speed is controlled at 800-1200 rpm, and the mixing time is 10-15 min, so that calcium stearate is uniformly coated on the surface of sodium bicarbonate particles; the mixed material is transferred to a cooling pan and naturally cooled to 25±5℃, and then passed through a 100-mesh sieve to obtain the final product.
[0024] In this embodiment of the invention, the preparation method of modified azodicarbonamide activated by zinc oxide is as follows: azodicarbonamide and 2-5% of its mass of nano zinc oxide are put into a high-speed mixer and mixed at 20-40℃ and 500-1000 rpm for 10-20 min, and then discharged to obtain the product.
[0025] In this embodiment of the invention, the sepiolite powder is obtained by crushing marine sedimentary sepiolite to 300-400 mesh.
[0026] Example 1 This embodiment provides a thermal insulation material containing expanded polystyrene, which is made from the following raw materials in parts by weight: 45 parts expanded polystyrene, 12 parts composite flame retardant, 5 parts reinforcing filler, 4 parts composite foaming agent, 2 parts lubricant, and 1 part antioxidant. The composite flame retardant has a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell; the preparation method of the composite flame retardant includes the following steps: (1) Calcium carbonate was dried at 200℃ for 2 hours to remove surface adsorbed water and obtain activated calcium carbonate; (2) Disperse the activated calcium carbonate obtained in step (1) in a 5% phosphoric acid solution at a solid-liquid ratio of 1:5, add 1% hexadecyltrimethylammonium bromide by mass of calcium carbonate, stir at 60°C for 2 hours to allow the calcium carbonate surface to undergo acid-base neutralization precipitation reaction with phosphoric acid, and generate a calcium phosphate coating layer in situ on the surface of calcium carbonate particles, forming a core-shell intermediate with calcium carbonate as the core and calcium phosphate as the shell. Filter, wash and dry to obtain phosphoric acid calcium carbonate; (3) The calcium carbonate phosphate obtained in step (2) is ultrasonically dispersed in anhydrous ethanol at a solid-liquid ratio of 1:8. 5% sepiolite powder and 1% γ-aminopropyltriethoxysilane are added. The mixture is stirred at 50°C for 3 hours to anchor the sepiolite powder on the calcium phosphate layer on the surface of the calcium carbonate phosphate, forming a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell. The mixture is then filtered, washed, and dried to obtain the final product.
[0027] The reinforcing filler is glass fiber; the lubricant is zinc stearate; and the antioxidant is antioxidant 1010.
[0028] The composite foaming agent is composed of azodicarbonamide and sodium bicarbonate in a mass ratio of 1:0.3; the sodium bicarbonate is modified sodium bicarbonate with calcium stearate coated on the surface, and the coating amount of calcium stearate is 3% of the mass of sodium bicarbonate; the azodicarbonamide is modified azodicarbonamide activated by zinc oxide, and the content of zinc oxide is 2% of the mass of azodicarbonamide.
[0029] Example 2 This embodiment provides a thermal insulation material containing expanded polystyrene, which is made from the following raw materials in parts by weight: 65 parts expanded polystyrene, 25 parts composite flame retardant, 12 parts reinforcing filler, 8 parts composite foaming agent, 5 parts lubricant, and 3 parts antioxidant. The composite flame retardant has a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell; the preparation method of the composite flame retardant includes the following steps: (1) Calcium carbonate was dried at 300℃ for 4 hours to remove surface adsorbed water and obtain activated calcium carbonate; (2) Disperse the activated calcium carbonate obtained in step (1) in a 20% phosphoric acid solution at a solid-liquid ratio of 1:10, add 5% hexadecyltrimethylammonium bromide by mass of calcium carbonate, stir at 90°C for 6 hours to allow the calcium carbonate surface to undergo acid-base neutralization precipitation reaction with phosphoric acid, and generate a calcium phosphate coating layer in situ on the surface of calcium carbonate particles, forming a core-shell intermediate with calcium carbonate as the core and calcium phosphate as the shell. Filter, wash and dry to obtain phosphoric acid calcium carbonate; (3) The calcium carbonate phosphate obtained in step (2) is ultrasonically dispersed in anhydrous ethanol at a solid-liquid ratio of 1:12. 15% sepiolite powder and 3% γ-aminopropyltriethoxysilane are added. The mixture is stirred at 70°C for 6 hours to anchor the sepiolite powder on the calcium phosphate layer on the surface of the calcium carbonate phosphate, forming a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell. The mixture is then filtered, washed, and dried to obtain the final product.
[0030] The reinforcing filler is SW-10 type wollastonite; the lubricant is calcium stearate; and the antioxidant is antioxidant 168.
[0031] The composite foaming agent is composed of azodicarbonamide and sodium bicarbonate in a mass ratio of 1:0.8; the sodium bicarbonate is modified sodium bicarbonate with calcium stearate coated on the surface, and the coating amount of calcium stearate is 8% of the mass of sodium bicarbonate; the azodicarbonamide is modified azodicarbonamide activated by zinc oxide, and the content of zinc oxide is 5% of the mass of azodicarbonamide.
[0032] Example 3 This embodiment provides a thermal insulation material containing expanded polystyrene, which is made from the following raw materials in parts by weight: 60 parts expanded polystyrene, 12 parts composite flame retardant, 6 parts reinforcing filler, 5 parts composite foaming agent, 3 parts lubricant, and 2 parts antioxidant. The composite flame retardant has a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell; the preparation method of the composite flame retardant includes the following steps: (1) Calcium carbonate was dried at 200℃ for 3 hours to remove surface adsorbed water and obtain activated calcium carbonate; (2) Disperse the activated calcium carbonate obtained in step (1) in a 10% phosphoric acid solution at a solid-liquid ratio of 1:6, add 2% hexadecyltrimethylammonium bromide by mass of calcium carbonate, stir at 90°C for 3 hours to allow the calcium carbonate surface to undergo acid-base neutralization precipitation reaction with phosphoric acid, and generate a calcium phosphate coating layer in situ on the surface of calcium carbonate particles, forming a core-shell intermediate with calcium carbonate as the core and calcium phosphate as the shell. Filter, wash and dry to obtain phosphoric acid calcium carbonate; (3) Disperse the calcium carbonate phosphate obtained in step (2) in anhydrous ethanol at a solid-liquid ratio of 1:10. Add 7% sepiolite powder and 2% γ-aminopropyltriethoxysilane by mass of calcium carbonate phosphate. Stir and react at 70°C for 4 hours to anchor the sepiolite powder on the calcium phosphate layer on the surface of calcium carbonate phosphate, forming a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell. Filter, wash, and dry to obtain the final product.
[0033] The reinforcing filler is SW-10 type wollastonite; the lubricant is zinc stearate; and the antioxidant is antioxidant 1010.
[0034] The composite foaming agent is composed of azodicarbonamide and sodium bicarbonate in a mass ratio of 1:0.5; the sodium bicarbonate is modified sodium bicarbonate with calcium stearate coated on the surface, and the coating amount of calcium stearate is 4% of the mass of sodium bicarbonate; the azodicarbonamide is modified azodicarbonamide activated by zinc oxide, and the content of zinc oxide is 3% of the mass of azodicarbonamide.
[0035] Example 4 This embodiment provides a method for preparing thermal insulation materials, including the following steps: Step 1: Premix the composite flame retardant and reinforcing filler in a high-speed mixer at 50-80℃ and 300-800rpm for 10-20min to obtain premix A; Step 2: Place expanded polystyrene, premix A, lubricant and antioxidant into the main feed port of a twin-screw extruder, melt blend at 170-190℃, control the screw speed at 150-250 rpm, establish melt strength, and obtain blend B; Step 3: Add the modified azodicarbonamide activated with zinc oxide through the first feed port of the twin-screw extruder, and add the modified sodium bicarbonate coated with calcium stearate through the second feed port of the twin-screw extruder. Control the die head temperature at 140-180℃, and then proceed with melt mixing, extrusion, foaming and shaping, cooling to 15-30℃, traction (traction speed of 1-2m / min), and cutting to obtain the final product.
[0036] Comparative Example 1 This comparative example is the same as Example 3, except that: the composite flame retardant has a double core-shell structure with calcium carbonate as the core and calcium phosphate as the shell, and does not contain sepiolite shell; its preparation method only includes steps (1) and (2) of the composite flame retardant preparation method in Example 3, that is, obtaining calcium carbonate phosphate. Everything else is the same as in Example 3.
[0037] Comparative Example 2 This comparative example is the same as Example 3, except that the composite flame retardant is replaced with an equal mass ratio of ordinary calcium carbonate, calcium phosphate, and sepiolite (1:1:1 mass ratio), and the three-layer core-shell structure preparation process is not used. Everything else remains the same as in Example 3.
[0038] Comparative Example 3 This comparative example is the same as Example 3, except that the composite foaming agent is replaced with equal parts by mass of unmodified ordinary azodicarbonamide and ordinary sodium bicarbonate (mass ratio 1:0.5), and zinc oxide activation and calcium stearate coating modification are not performed. Everything else remains the same as in Example 3.
[0039] Effect verification The performance of the thermal insulation materials prepared according to Example 4 in Examples 1-3 and Comparative Examples 1-3 was tested, and the performance test results are shown in Table 1. The cell morphology characterization method was as follows: samples were taken from the thermal insulation material, frozen with liquid nitrogen, and then fractured. The fracture surface was purged with high-pressure compressed air to remove attached debris. The samples were then sputtered with gold (sputtering time 60-120s, current 10-20mA), and the cell structure of the sample cross-section was observed using a field emission scanning electron microscope.
[0040] Table 1
[0041] As shown in Table 1, the expanded polystyrene insulation materials prepared in Examples 1-3 of this invention have thermal conductivity of 0.030-0.032 W / (m·K), a flame retardancy rating of B1, and a uniform and dense cell structure, achieving a good balance between thermal insulation and flame retardancy. In contrast, the thermal conductivity of Comparative Example 1 increased to 0.036 W / (m·K), the flame retardancy rating decreased to B2, and the cells showed partial enlargement and uneven distribution, indicating that the sepiolite shell plays an irreplaceable key role in cell nucleation and flame retardancy enhancement. The thermal conductivity of Comparative Example 2 further increased to 0.037 W / (m·K), the cells became significantly larger and showed fused pores, and the flame retardancy rating was B2, indicating that the three-layer core-shell structure of this invention is significantly superior to simple physical blending of the components. Comparative Example 3 exhibited the highest thermal conductivity, reaching 0.040 W / (m·K), but its cells were extremely irregular, with numerous collapsed bubbles and overall non-uniformity. Its flame retardancy rating was only B2. This demonstrates that the targeted modification of the foaming agent and its combination with the two-stage side-feeding process played a decisive role in constructing a homogeneous microporous structure and maintaining a low thermal conductivity. In summary, Example 3 achieved the best overall performance with a thermal conductivity of 0.030 W / (m·K), a flame retardancy rating of B1, and the finest and most uniform cell structure.
[0042] It is noteworthy that Example 2, even with a composite flame retardant addition of up to 25 parts, still maintained a low thermal conductivity and a B1 flame retardant rating. This overcomes the traditional understanding that adding flame retardants impairs insulation. The reason is that the sepiolite shell in the composite flame retardant of this invention not only provides flame retardant properties but also acts as a highly efficient cell nucleating agent. Its effect increases with dosage, thus inducing the formation of a fine and uniform cell structure even at higher filling amounts, effectively offsetting the negative impact of increased solid content on thermal conductivity. Comparative Example 1, on the other hand, demonstrates from the opposite perspective that without the nucleating effect of the sepiolite shell, even with only 12 parts of flame retardant added, the thermal conductivity of the material would significantly increase to 0.036 W / (m·K). This fully illustrates the indispensable key role of the three-layer core-shell structure described in this invention in simultaneously achieving high flame retardancy and low thermal conductivity.
[0043] It should be understood that the disclosed invention is not limited to the specific methods, schemes, and substances described, as these are all subject to variation. It should also be understood that the terminology used herein is for the purpose of describing specific embodiments only and is not intended to limit the scope of the invention, which is limited only by the appended claims.
Claims
1. A thermal insulation material containing expanded polystyrene, characterized in that, It is made from the following raw materials in parts by weight: 45-65 parts expanded polystyrene, 12-25 parts composite flame retardant, 5-12 parts reinforcing filler, 4-8 parts composite foaming agent, 2-5 parts lubricant, and 1-3 parts antioxidant. The composite flame retardant has a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell.
2. The thermal insulation material according to claim 1, characterized in that, The preparation method of the composite flame retardant includes the following steps: (1) Calcium carbonate is dried at 200-300℃ for 2-4 hours to obtain activated calcium carbonate; (2) Disperse the activated calcium carbonate obtained in step (1) in a phosphoric acid solution with a mass concentration of 5-20% at a solid-liquid ratio of 1:5-10, add hexadecyltrimethylammonium bromide at a mass of 1-5% of calcium carbonate, stir and react at 60-90℃ for 2-6 hours to form a core-shell intermediate with calcium carbonate as the core and calcium phosphate as the shell, filter, wash and dry to obtain phosphorylated calcium carbonate; (3) Disperse the calcium carbonate phosphate obtained in step (2) in anhydrous ethanol at a solid-liquid ratio of 1:8-12. Add 5-15% sepiolite powder and 1-3% γ-aminopropyltriethoxysilane by mass of calcium carbonate phosphate. Stir and react at 50-70℃ for 3-6 hours to form a three-layer core-shell structure with calcium carbonate as the core, calcium phosphate as the inner shell, and sepiolite as the outer shell. Filter, wash, and dry to obtain the final product.
3. The thermal insulation material according to claim 1, characterized in that, The reinforcing filler is selected from one or more of glass fiber and wollastonite.
4. The thermal insulation material according to claim 1, characterized in that, The composite foaming agent is composed of azodicarbonamide and sodium bicarbonate in a mass ratio of 1:0.3-0.
8.
5. The thermal insulation material according to claim 4, characterized in that, The sodium bicarbonate is a modified sodium bicarbonate with calcium stearate coated on its surface, and the amount of calcium stearate coating is 3-8% of the mass of sodium bicarbonate. The azodicarbonamide is a modified azodicarbonamide activated by zinc oxide, and the content of zinc oxide is 2-5% of the mass of the azodicarbonamide.
6. The thermal insulation material according to claim 1, characterized in that, The lubricant is selected from one or more of zinc stearate and calcium stearate.
7. The thermal insulation material according to claim 1, characterized in that, The antioxidant is selected from one or more of antioxidant 1010 and antioxidant 168.
8. A method for preparing the thermal insulation material according to any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Premix the composite flame retardant and reinforcing filler in a high-speed mixer at 50-80℃ for 10-20 minutes to obtain premix A; Step 2: Place expanded polystyrene, premix A, lubricant and antioxidant into the main feed port of a twin-screw extruder and melt-blend at 170-190℃ to obtain blend B; Step 3: Add the modified azodicarbonamide activated with zinc oxide through the first feed port of the twin-screw extruder, and add the modified sodium bicarbonate coated with calcium stearate through the second feed port of the twin-screw extruder. Control the die head temperature at 140-180℃, and then proceed with melt mixing, extrusion, foaming and shaping, cooling, traction and cutting to obtain the final product.
9. The use of the thermal insulation material according to any one of claims 1-7 in the preparation of thermal insulation components.
10. The application of the thermal insulation material according to any one of claims 1-7 in improving the flame retardant properties of thermal insulation components.